2022
DOI: 10.1186/s12968-022-00881-1
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-specific reference values of biventricular strain and strain rate derived from a large cohort of healthy Chinese adults: a cardiovascular magnetic resonance feature tracking study

Abstract: Background As a noninvasive tool, myocardial deformation imaging may facilitate the early detection of cardiac dysfunction. However, normal reference ranges of myocardial strain and strain rate (SR) based on large-scale East Asian populations are still lacking. This study aimed to provide reference values of left ventricular (LV) and right ventricular (RV) strain and SR based on a large cohort of healthy Chinese adults using cardiovascular magnetic resonance (CMR) feature tracking (FT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
3
3
0
Order By: Relevance
“…Of note, our article is the only one to calculate radial strain from both long-axis and short-axis planes, while, in almost all previous studies, horizontal long-axis cines were tracked to derive longitudinal strain, while short-axis cines were used to derive circumferential and radial strain. Moreover, the gender differences in myocardial strain are in agreement with previous studies [ 11 , 12 , 13 ], while the relationship between age and strain values has shown conflicting results. In particular, differently from our results, several previous studies reported an age-related increase in LV GCS [ 11 , 12 , 13 ], LV GRS [ 12 , 13 , 14 ], and all RV strains [ 13 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Of note, our article is the only one to calculate radial strain from both long-axis and short-axis planes, while, in almost all previous studies, horizontal long-axis cines were tracked to derive longitudinal strain, while short-axis cines were used to derive circumferential and radial strain. Moreover, the gender differences in myocardial strain are in agreement with previous studies [ 11 , 12 , 13 ], while the relationship between age and strain values has shown conflicting results. In particular, differently from our results, several previous studies reported an age-related increase in LV GCS [ 11 , 12 , 13 ], LV GRS [ 12 , 13 , 14 ], and all RV strains [ 13 ].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the gender differences in myocardial strain are in agreement with previous studies [ 11 , 12 , 13 ], while the relationship between age and strain values has shown conflicting results. In particular, differently from our results, several previous studies reported an age-related increase in LV GCS [ 11 , 12 , 13 ], LV GRS [ 12 , 13 , 14 ], and all RV strains [ 13 ]. On the other hand, in children, all global LV strains showed a significant parabolic relation to age and an even stronger one to BSA, but no gender differences [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Women with acromegaly, like women in the general population, have better GLS compared to men ( 30 ). Similar observations had researchers evaluating the heart of athletes by STE.…”
Section: Discussionmentioning
confidence: 99%
“…Before the first chemotherapy, we compared the baseline values of the subjects with those of normal people in the previous studies [16][17][18] to exclude abnormal subjects.…”
Section: Study Populationmentioning
confidence: 99%